THE URGENCY OF ARTIFICIAL INTELLIGENCE REGULATION FROM A JOINT AUTHORSHIP PERSPECTIVE ON COPYRIGHT INFRINGEMENT - Subagiyo, Dwi Tatak; Wibisono, Hari (Indonesia Private Law Review, 2024)
This research, titled Urgency of Artificial Intelligence Regulation from the Perspective of Joint Authorship Against Copyright Infringement, aims to analyze the legal framework governing Artificial Intelligence (AI)-based creations in Indonesia and explore the application of the Joint Authorship perspective to AI-generated works. Using a normative legal methodology, the research focuses on library research involving laws, regulations, and related literature. The findings reveal that Indonesia's Copyright Law No. 28 of 2014 does not adequately address AI-based creations. Specifically, Articles 58 and 59, which reference the "death of the creator," imply that creators are human, creating ambiguity as AI lacks human cognitive abilities and cannot meet the necessary criteria for copyright protection. Additionally, the research suggests that applying the Joint Authorship perspective to AI-generated works could recognize them as collaborative efforts between humans and computer programs. This approach would benefit creators by ensuring shared copyright and acknowledging the contributions of both humans and AI systems in the creation process.